ANALISA PROSES KOMUNIKASI PARIWISATA BERBASIS MODERASI BERAGAMA DI DESA WISATA SADE LOMBOK TENGAH - Jelantik, Sayu Kadek; Astraguna, I Wayan (Institut Agama Hindu Negeri Gde Puda Mataram, 2023)
Tourism communication activity, namely conveying tourism messages in the form of tourism products in Sade Tourism Village, aims to analyze the communication process that occurs with the study of Berlo's S-M-C-R theory. The research method used is descriptive qualitative research with primary data, namely tourism activists and tourists who occur in Sade Tourism Village. This study analyzes the tourism communication process that applies the values ​​of religious moderation that occur in Sade Tourism Village, Central Lombok. The analysis used uses Berlo's S-M-C-R theory, namely there are 4 important elements in the tourism communication process, namely: the first element of the source is the sender of messages by tourism activists in Sade Tourism Village in the form of tourism products from direct or indirect communication in the form of art performances. The source or travel message sender has good communication skills and good cultural understanding. The second element is a tourist massage (message) sent in the form of non-verbal messages and verbal messages. The third element is the channel or media used in the communication process, which refers to the five senses, namely sight, hearing, taste when enjoying tourism products in the Sade tourism village. The fourth element is the receiver or recipient of tourism messages, namely tourists, tourism products are received with good communication skills by tourists and good cultural knowledge.